Síntese e caracterização de materiais do sistema ternário SiO2-ZnO-TiO2 obtido por sol-gel/Pechini - Fógia, Michelly Patrícia Santana de Almeida (2014)
In this work the structural and optical properties of SiO2-ZnO-TiO2 system doped with of Eu3+ (1% in mol) or Er3+ ions (0,2% to 2,0% in mol) were investigated. The compositions xSiO2-([100-x]/2)ZnO-([100-x]/2)TiO2 with x ranging from 40 to 80 were synthesized and studied. A mixed methodology using the traditional sol-gel process and Pechini method was employed to prepare stable and transparent sols, homogeneous gels, powders and transparent thin films without cracks. The prepared powders were heat treated from 100°C to 1100°C. The optical “band gap” values, the lifetime of Eu3+ 5D0 level, the R/O ratio of Eu3+ emissions and refractive index are dependent on the composition and thermal treatment of the powders. Multilayered thin films were deposited onto silica substrates using the “spin coating” technique. Afterwards, the as-prepared thin films were calcined at 500°C followed by annealings from 700°C to 1000°C. The X-ray diffraction of powders showed that the crystallization starts at 800°C with a mixture of zinc titanate phases (ZnTiO3, Zn2TiO4) and titanium rutile (TiO2). In compositions with low silica content (x = 40 or 50) the formation of zinc silicate (Zn2SiO4) occurs at high temperatures. The optical properties were evaluated for both powders and thin films. Particularly, thin films exhibit transmittance above 80% in the visible region. The refractive index at 632.8 nm and thickness of thin films were estimated using the envelope method and m-Line spectrocopy. Furthermore, morphological analysis of the thin films surface was performed by scanning electron microscopy. The characteristic emission peaks of Er3+ or Eu3+ doped powders and thin films were measured. The photoluminescent emission of Eu3+ ions, obtained the highest intensities for the powders treated at 800°C, for films treated at 700°C, under excitation at 394 nm, where the system remains primarily amorphous. The photoluminescent emission of the Er3+ ions was more intense for the powders treated at 1100°C under excitation at 980 nm, mainly due to reduction of hydroxyl groups which act as photoluminescence quenchers. In the film the highest intensity occurred at a temperature of 700°C under excitation at 378 nm and showing only one guided mode. Thus, the obtained thin films can be suitable for application as waveguides in integrated optical systems. Moreover, the Eu and Er doped powders can be used as phosphors in displays.